2020
DOI: 10.1177/1071181320641416
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of workload demands imposed by different types of distracted walking tasks and its effect on gait

Abstract: A growing body of research has found that distracted walking is a safety concern due to reduced situation awareness and the possibility of compromised gait performance. Distraction tasks, such as texting, browsing social media, and playing games, differ in terms of their physical and cognitive demands. However, few studies have examined whether there are differences in how physical and cognitive demands impact gait. The goal of this paper is to evaluate workload differences between four distraction tasks that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The three phone tasks were intended to simulate tasks with varying levels of workloads. The tapping task, which simulates dialing or texting, was shown to have a larger physiological workload as well as a higher visual demand (Zheng et al, 2020). The gaming task was designed to replicate a challenging working memory task, and it necessitates a greater physiological workload as well as a larger cognitive workload (Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The three phone tasks were intended to simulate tasks with varying levels of workloads. The tapping task, which simulates dialing or texting, was shown to have a larger physiological workload as well as a higher visual demand (Zheng et al, 2020). The gaming task was designed to replicate a challenging working memory task, and it necessitates a greater physiological workload as well as a larger cognitive workload (Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These phone tasks represent common activities that individuals perform with their phones, with reading corresponding to browsing of information, tapping representing typing or dialing phone numbers, and the N-back game representing more difficult memory tasks, such as memorizing two-factor authentication codes. Our previous study (Zheng et al, 2020) has shown that between these three phone tasks, the N-back game is the most mentally demanding, while reading is the least mentally demanding.…”
Section: Experimental Designmentioning
confidence: 95%
See 2 more Smart Citations
“…At last, older adults often suffer from chronic diseases (e.g., Alzheimer's disease, Cataracts, & Glaucoma); hence, it is also worthwhile to consider chronic diseases, especially eye diseases, as a factor that influences gait characteristics in different light conditions. Finally, it has been reported that numerous environmental and implicit factors such as the landscape of the walking surface (Hu et al, 2018) and mental distraction (Zheng et al, 2020) can all influence gait performance under normal lighting conditions. How these factors affect human gait in the dark environment merits further investigation.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%